Pengaruh Review Online, Kepercayaan Pada Web, Keamanan Bertransaksi Online, dan Privasi Terhadap Niat Pembelian Ulang Pada Toko Online Lazada - Aulia Maya Nur Lita; Zakky Fahma Auliya (EBBANK, 2019)
The purpose of this study was to determine the effect of online reviews, trust in the web, securityy of online transactions, and privacy toward repurchase intention on Lazada’s online store. The type of research used in this study is quantitative. The population in this study was the community of Solo Raya who had made an online purchase at Lazada. The sampling technique uses nonprobability sampling with incidental sampling techniques. In conducting data processing, this study uses SPSS 23. This research uses a questionnaire as material for collecting data with a sample of 100 respondents. This study uses multiple linear regression analysis. This analysis is used to test the relationship between the independent variable and the dependent variable. The results of this study are (1) Online reviews have no significant effect on repurchase intention, (2) Trust in the web has a significant effect on repurchase intention, (3) The security of online transactions has an effect on repurchase intention, (4) Privacy has a significant effect on repurchase intention